(untitled) (International Journal of Engineering and Computer Science, 2014)
As fire is the test of gold, being patient is the test of men, so is the testing is the test of assessing the quality of the product!!!” With the development of Fourth generation languages (4GL), the proportion of time devoted to testing has been increased and is truly effective means. Testing technique research leads to the destination of practical testing methods and tools. Progress toward this destination requires fundamental research, and the creation, refinement, extension, and popularization of better methods. The methodology for the paper is case study of our college (Sophia Girls’ College) Office Automation Software. Our study focuses on the state of the art in testing techniques, as well as the latest techniques which representing the future direction of this area.